2016
DOI: 10.1038/srep24976
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in follicular fluid, powerful tools to explore in vitro fertilization process

Abstract: Circulating or “extracellular” microRNAs (miRNAs) detected in biological fluids, could be used as potential diagnostic and prognostic biomarkers of several disease, such as cancer, gynecological and pregnancy disorders. However, their contributions in female infertility and in vitro fertilization (IVF) remain unknown. This study investigated the expression profiles of five circulating miRNAs (let-7b, miR-29a, miR-30a, miR-140 and miR-320a) in human follicular fluid from 91 women with normal ovarian reserve and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 57 publications
2
66
0
Order By: Relevance
“…In recent years, miR-140 has been reported to exhibit significant regulatory effects with respect to cell proliferation, differentiation, migration, and invasion [11][12][13]. Scalici et al showed that the expression of miR-140 in the follicular fluid was different between PCOS and normal ovarian reserves, with a specificity of 83.8% and a sensitivity of 70% [14]. However, the expression profile of miR-140-along with its underlying mechanism during ovarian dysfunction-is still poorly reported.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, miR-140 has been reported to exhibit significant regulatory effects with respect to cell proliferation, differentiation, migration, and invasion [11][12][13]. Scalici et al showed that the expression of miR-140 in the follicular fluid was different between PCOS and normal ovarian reserves, with a specificity of 83.8% and a sensitivity of 70% [14]. However, the expression profile of miR-140-along with its underlying mechanism during ovarian dysfunction-is still poorly reported.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 28 articles included, 18 evaluated the miRNAs in ovaries and/or extracellular vesicles (i.e., exosomes and microvesicles) [9,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]; three in oocytes [33][34][35]; and seven in embryos [36][37][38][39][40][41][42].…”
Section: Summary Of Selected Studiesmentioning
confidence: 99%
“…The other four articles explored a small number of miRNAs in PCOS patients, all using qRT-PCR. One of these studies compared the expression of five miRNAs in the follicular fluid between 30 women with PCOS and 91 women with normal ovarian reserve (NOR; as controls), and found that miR-30a was significantly up-regulated and miR-140 and let-7b were significantly down-regulated in the follicular fluid from patients with PCOS compared with women with NOR [18]. Another work investigated, by comparing women suffering from PCOS (n = 25) with women without PCOS (n = 20), the effects of miR-145 on cell proliferation and its underlying mechanism in isolated human granulosa cells from aspirated follicular fluid.…”
Section: /14mentioning
confidence: 99%
“…Sang et al first reported that the supernatant, microvesicles or exosomes from cell-free human follicular fluid contain miRNAs, which are important in metabolic and reproductive signaling pathways (Sang et al 2013). Moreover, the miRNAs in human follicular fluid are powerful tools in the in vitro fertilization (IVF) process, which can predict the development of expanded blastocysts and clinical pregnancy outcome (Scalici et al 2016). However, there have been few studies concerning the relationship between miRNAs in human follicular fluid and the pathogenesis of PCOS.…”
Section: Introductionmentioning
confidence: 99%